Gravity Solutions in the Cloud: A Repository of General Relativity Computations. - Maxwell, Morgan; Ray, Joseph; Rodriguez, Maria J.; Temoche, Luis Fernando (Journal of the Utah Academy of Sciences, Arts & Letters, 2025)
The goal of this project is to create a public repository that provides access to important software related to differential calculus and the general relativistic solutions of Einstein’s equations. This unique repository, in Wolfram coding language ‚ aims to ensure reliable access and maintenance of essential software packages, including the EDCGRTC code, while providing an introduction to the physical properties of gravitational systems within this framework. Additionally, we will perform detailed computations on gravitational solutions to Einstein’s equations to extract key observables, such as the location of singularities in these systems and the computation of their associated conserved charges.